"I don't know how to spell it": Overcoming Translingual Spelling Hesitancy. (23rd March 2022) - Rowe, Lindsey W.
Abstract: Teachers in English‐medium classrooms can support students' translingual composing by inviting students to write using all their language resources. However, students in these contexts often express hesitancy about their ability to spell in languages beyond English. This article describes support strategies teachers can use to scaffold students' translingual composing and help them overcome hesitancy about spelling in languages beyond English. These support strategies center on helping students draw on available resources, including their existing knowledge, peers and family members, and digital tools to write/spell in languages beyond English.